(untitled) (European Journal of Pure and Applied Mathematics, 2024)
Our main purpose is to introduce the notion of weakly quasi (τ_1,τ_2)-continuous multifunctions. Furthermore, several characterizations of almost quasi (τ_1,τ_2)-continuous multifunctions are established.